Does selective logging stress tropical forest invertebrates? Using fat stores to examine sublethal responses in dung beetles. Issue 23 (4th November 2016) - França, Filipe; Barlow, Jos; Araújo, Bárbara; Louzada, Julio
Abstract: The increased global demand for tropical timber has driven vast expanses of tropical forests to be selectively logged worldwide. While logging impacts on wildlife are predicted to change species distribution and abundance, the underlying physiological responses are poorly understood. Although there is a growing consensus that selective logging impacts on natural populations start with individual stress‐induced sublethal responses, this literature is dominated by investigations conducted with vertebrates from temperate zones. Moreover, the sublethal effects of human‐induced forest disturbance on tropical invertebrates have never been examined. To help address this knowledge gap, we examined the body fat content and relative abundance of three dung beetle species (Coleoptera: Scarabaeinae) with minimum abundance of 40 individuals within each examined treatment level. These were sampled across 34 plots in a before‐after control‐impact design (BACI) in a timber concession area of the Brazilian Amazon. For the first time, we present evidence of logging‐induced physiological stress responses in tropical invertebrates. Selective logging increased the individual levels of fat storage and reduced the relative abundance of two dung beetle species. Given this qualitative similarity, we support the measurement of body fat content as reliable biomarker to assess stress‐induced sublethal effects on dung beetles. Understanding how environmental modification impacts the wildlife has never been more important. Our novel approach provides new insights into the mechanisms through which forest disturbances impose population‐level impacts on tropical invertebrates. Abstract : Understanding how environmental degradation affects the wildlife has never been more pressing. By examining the sublethal impacts of selective logging on the body fat content from Amazonian dung beetles, our study shows, for the first time, that human‐driven forest degradation brings about stress‐induced physiological effects on tropical invertebrates.